DAYA TARIK FACEBOOK SEBAGAI MEDIA KOMUNIKASI ALTERNATIF - Marlina Marlina (Al-Balagh : Jurnal Komunikasi Islam, 2016)
Communication is a necessity that can not be avoided by human being, since communication is also a primary needs for every social creatures. Nowadays, we find on each social status; regardless of social status, education level and occupation then communication takes place on the virtual world, with social media facilities that are very diverse, therefore the communications made by each person more easily and quickly. They will find new friends there, old friends who had not seen a long time, and others. Observing every detail of the text that used by social media user when interacting with friends on "virtual world", will be seen how much their kindness and sincerity in social interactions through the virtual world. This study was conducted by using interview techniques to  10 users of facebook. This is a qualitative study that used a theory of interpersonal communication. The finding in this study was that communication which  done directly face to face is on going replaced by communication  through the social media, especially  Facebook. The social media users are more happy and fun to greet each other virtually, even when they were sitting together, they more enjoy with interaction on virtual world with others. In this study, it can also be found some factors that cause the shifting of face to face communication pattern  into communication via Facebook. There are some factors namely: the distance between them, their own duty then it is impossible to meet, more relaxed and can be done in any case, the language can be set in such a way and low cost. Nevertheless, personal communication by face to face is a manifestation of the real communication, while the communication which  done by social media is an alternative way of communicating with no disturbing and more saving